Peningkatan Motivasi dan Hasil Belajar Kognitif Kelas X melalui Model Problem Based Learning - Rahma Dita Dewayani; Atip Nurwahyunani; Edy Priyanta (Jurnal Pendidikan Guru Profesional, 2024)
Learning outcomes are students' abilities that have been achieved after following a learning process that includes cognitive, affective and psychomotor aspects. Student learning outcomes are influenced by several factors, both internal and external factors. Internal factors are factors that originate from students themselves which can influence learning outcomes, one of which is students' learning motivation. The problem based learning model is designed to guide active learning and critical thinking. In PBL, students who are faced with problems are required to be able to explore for themselves through observation skills, arguing in discussions, and carrying out practices in accordance with scientific procedures. Based on the results of observations in class X7 of SMA Negeri 10 Semarang, the majority of students were still passive during learning activities. This became the background for carrying out classroom action research regarding increasing student motivation and learning outcomes through the problem based learning model. This research method is PTK with a model according to Kemmis & McTaggart which consists of three stages, namely planning, implementation and observation, and reflection. Data collection techniques include observation, distributing questionnaires, and evaluation questions in the form of daily assessments. The research results showed that there was an increase in learning motivation with a percentage of 72% in cycle I to 83% in cycle II. Furthermore, the percentage of completeness of student learning outcomes in cycle I was 77% and cycle II increased to 94%. Thus, it can be concluded that there is an increase in motivation and learning outcomes for viral material through the Problem Based Learning model.